Posterior white matter integrity and self-reported posterior cortical symptoms using the Colorado Posterior Cortical Questionnaire - Holden, Samantha K.; Bettcher, Brianne M.; Filley, Christopher M.; Lopez-Paniagua, Dan; Pelak, Victoria S. (Frontiers in Neurology, 2023)
Background The Colorado Posterior Cortical Questionnaire (CPC-Q) is a self-report, 15-item screening questionnaire for posterior cortical symptoms, including visuospatial and visuoperceptual difficulties. Changes in white matter connectivity may precede obvious gray matter atrophy in neurodegenerative conditions, especially posterior cortical atrophy. Integration of CPC-Q scores and measures of white matter integrity could contribute to earlier detection of posterior cortical syndromes. Methods We investigated the relationships between posterior cortical symptoms as captured by the CPC-Q and diffusion tensor imaging fractional anisotropy (DTI FA) of white matter regions of interest localized to posterior brain regions (posterior thalamic radiations, splenium of corpus callosum, tapetum). Comparisons were also made by diagnostic group [healthy older adult (n = 31), amnestic Alzheimer's disease (AD, n = 18), and posterior cortical atrophy (PCA, n = 9)] and by SENAS battery visuospatial composite score quartile. Exploratory comparisons of all available individual white matter region DTI FA to CPC-Q, as well as comparisons of DTI FA between diagnostic groups and visuospatial quartiles, were also made. Results CPC-Q score was correlated with the average DTI FA for the averaged posterior white matter regions of interest (r = −0.31, p = 0.02). Posterior thalamic radiation DTI FA was most strongly associated with CPC-Q (r = −0.34, p = 0.01) and visuospatial composite (r = 0.58, p < 0.01) scores and differed between the PCA and AD groups and the lower and higher visuospatial quartiles. The DTI FA of body and splenium of the corpus callosum also demonstrated this pattern but not the DTI FA of the tapetum. Conclusion The integrity of posterior white matter tracts is associated with scores on the CPC-Q, adding to the validation evidence for this new questionnaire. White matter regions that may be related to posterior cortical symptoms detected by the CPC-Q, and distinct from those affected in amnestic syndromes, include the posterior thalamic radiations and body and splenium of the corpus callosum. These findings are in line with previous neuroimaging studies of PCA and support continued research on white matter in posterior cortical dysfunction.